Hot-injection synthesis of lead-free pseudo-alkali metal-based perovskite (TlSnX3) nanoparticles with tunable optical properties - Kim, Wooyeon; Koo, Bonkee; Ko, Min Jae; Jung, Heesuk (Frontiers in Materials, 2023)
The commercialization of organo-inorganic hybrid perovskite materials for optoelectronic applications is limited owing to the restriction of lead (Pb) usage in consumer electronics and the instability of organic cations in the perovskite structure. To address these challenges, we synthesize TlSnX3 (X = Cl, Br, and I) perovskite nanoparticles (NPs) with high crystallinity and uniformity using the hot-injection method. The optical properties of TlSnX3NPs are fine-tuned by substituting the halide ions of TlSnX3. In addition, the oxidation of Sn in TlSnX3 NPs is effectively prevented by the strong reducing ligands such as dioleamide (DOA) and trioctylphosphine (TOP). Furthermore, TlSnX3 NPs-based perovskite solar cells (PSCs) are fabricated by a spin-coating method; they exhibited a high open-circuit voltage (~1.4 V). These results demonstrate that TlSnX3 NPs can be an attractive candidate for solution-processable optoelectronic devices.